Biomass Burning Aerosols Observed in Northern Finland during the 2010 Wildfires in Russia - Tero Mielonen; Veijo Aaltonen; Heikki Lihavainen; Antti-Pekka Hyvärinen; Antti Arola; Mika Komppula; Rigel Kivi (Atmosphere, 2013)
A smoke plume originating from the massive wildfires near Moscow was clearly detected in northern Finland on 30 July 2010. Measurements made with remote sensing instruments demonstrated how the biomass burning aerosols affected the chemical and optical characteristics of the atmosphere in regions hundreds of kilometers away from the actual fires. In this study, we used MODIS, AIRS, CALIOP, PFR, ceilometers, FTS and Brewer data to quantify the properties of the transported smoke plume. In addition, in situ measurements of aerosol concentration (DMPS), absorption (aethalometer) and scattering (nephelometer) are presented. We found that due to the smoke plume in northern Finland, the daily averaged optical thickness of aerosols increased fourfold, and MODIS retrieved AOD as high as 4.5 for the thickest part of the plume. FTS measurements showed that CO concentration increased by 100% during the plume. CALIOP and ceilometer measurements revealed that the smoke plume was located close to the surface, below 3 km, and that the plume was not homogeneously mixed. In addition, in situ measurements showed that the scattering and absorption coefficients were almost 20 times larger in the smoke plume than on average, and that the number of particles larger than 320 nm increased 14-fold. Moreover, a comparison with in situ measurements recorded in eastern Finland on the previous day showed that the transport from eastern to northern Finland decreased the scattering coefficient, black carbon concentration, and total number concentration 0.5%/h, 1.5%/h and 2.0%/h, respectively.